ANALISIS KARAKTER DAN LATAR PADA CERPEN “JANJI SANG PENARI” KARYA NYOMAN TUSTHI EDDY - Sinta Sinta; Wikanengsih Wikanengsih; Agus Priyanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study aims to examine the characters and settings in Nyoman Tusthi Eddy's short story "Janji Sang Penari" and to analyze the characters in the short story and to find the name of the setting for the time, place, and atmosphere of the short story. The research method used by the author in this study is a qualitative descriptive method. This research was conducted by first reading a short story entitled "Janji Sang Penari" by Nyoman Tusthi Eddy, then analyzing the characters and settings contained in the short story text. From the analysis of the short stories, the writer found various characters and backgrounds contained in the short story "Janji Sang Penari" by Nyoman Tusthi Eddy. There are 5 characters in the short story, namely Wilastri, Wilastri's father, dance teacher, Wilastri's girlfriend, and Wilastri's mother. The characters in the short story are a beautiful woman, a dancer, obedient to behavior, a wise man, a man who is innocent, doesn't talk much, and a mother who always gives advice. While the background of the short story is the Balinese socio-cultural background which is still thick and strong. The time setting for the short story is during the ceremony. The setting for the short story is Pura Desa in Bali, the arena, the sea, and Wilastri's house. While the background of the atmosphere in the short story is cool, peaceful, calm, grief, blue touched.